Effect of sodium-glucose cotransporter-2 inhibitor on metabolic syndrome in people with prediabetes and obesity: A systematic review and meta-analysis - Sadia Bari; Afroza Rahman; Md Anwar Hossen; KM Saif-Ur-Rahman (Health Sciences Review)
Sodium-glucose cotransporter-2 (SGLT2) inhibitors have emerged as a novel therapeutic approach for managing type 2 diabetes mellitus (T2DM), offering benefits that extend beyond glycaemic control. This systematic review aims to examine the effects of SGLT2 inhibitors on metabolic syndrome in individuals with prediabetes and obesity. We conducted a comprehensive search across PubMed, EMBASE, Cochrane Library, Web of Science (Core Collection), and Scopus. Title and abstract screening, data extraction, and risk of bias (ROB) assessment were performed independently by two reviewers. ROB was assessed using the Cochrane Risk of Bias tool. A meta-analysis was conducted using a random-effects model.Our meta-analysis did not show statistically significant reductions in body weight (mean difference: –3.05 kg; 95 % CI: –8.18 to 2.09), BMI (mean difference: –1.43 kg/m²; 95 % CI: –4.11 to 1.25), systolic blood pressure (mean difference: –2.12 mmHg; 95 % CI: –7.39 to 3.16), or diastolic blood pressure (mean difference: –1.04 mmHg; 95 % CI: –5.07 to 2.99) with dapagliflozin. However, a reduction was observed in fasting plasma glucose (mean difference: –0.47 mmol/L; 95 % CI: –0.90 to –0.05).Although current findings suggest that SGLT2 inhibitors (dapagliflozin) may have little to no impact on individual components of metabolic syndrome, the evidence remains limited. Further well-powered clinical trials are warranted to validate these observations. Future research should focus on comparing the efficacy of different SGLT2 inhibitors and exploring their potential synergistic effects when combined with other pharmacological agents in the treatment of metabolic syndrome.